Microbiological assessment of hamburger patties sold in selected burger stands in Iloilo City - Magpusao, Johannes M. (2006.)
The microbiological qualities of raw and cooked hamburger patties from the three selected mobile burger stands (identified as A, B, and C) in Iloilo City were evaluated from February 2 to April 8, 2006.
Thesis - B.S. (Food Technology) - SOTECH, University of the Philippines in the Visayas.
Keywords: Hamburger patties -- Microbiological Assessment; Iloilo City